Metagenomic and metatranscriptomic analysis of the microbial community structure and metabolic potential of fermented soybean in Yunnan Province - LIU,Xiao-Feng (2020)
Abstract Traditional fermented soybean contains a variety of microflora. To obtain a comprehensive and accurate understanding of the microbial community structure and metabolic potential of fermented soybean, comparative metagenomics and metatranscriptomics were performed on a sample of fermented soybean in Yunnan Province. Metagenomic DNA and metatranscriptomic RNA were sequenced using Illumina HiseqTM2500, which yielded a total of 92,192,276 reads, with an average read length of 150 bp and 38,798,262 paired-end sequences, with an average length of 151 bp. The results show that Providencia stuartii was the most abundant species and the genes of carbohydrates (2296, 13.30%), protein metabolism (1530, 8.86%), and amino acids and amino acid derivatives (1423, 8.24%) were dominant. The expression levels of the genes belonging to amino acid transport and metabolism processes were the highest according to the reads per length of transcript in kilo-bases per million mapped reads (RPKM) values, followed by energy production and conversion and carbohydrate transport and metabolism. The metabolic pathways were primarily associated with carbohydrates, proteins and amino acids, which might be in accordance with the high levels of proteins and other nutrients in soybeans. Overall, these findings provide insights into the community structure and metabolic potential of the fermented soybean microbiome.